What should we prepare for the next coronavirus disease 2019 outbreak? A survey on the opinions of infectious diseases specialists in South Korea - Kim, Bongyoung; Park, Se Yoon; Jung, Dong Sik; Jung, Sook In; Oh, Won Sup; Kim, Shin-Woo; Peck, Kyong Ran; Chang, Hyun-Ha (The Korean journal of internal medicine, 2020)
This study aimed to collect information on the opinions of Korean infectious disease (ID) experts on coronavirus disease 2019 (COVID-19) and related issues in preparation for a future outbreak. A survey was conducted over the course of 5 days (from April 21 to 25, 2020), targeting all adult ID specialists currently in the medical field in South Korea (n = 265). An online-based survey was forwarded via text message and e-mail. Only one response was accepted from each participant. Of these 265 ID specialists gotten to, 132 (49.8%) responded. The highest proportion of the respondents envisaged the current COVID-19 outbreak to end after December 2020 (47.7% for the domestic Korean outbreak and 70.5% for the global pandemic); moreover, 60.7% of them stated that a second nationwide wave is likely to occur between September and December 2020 in South Korea. N95 respirators were considered to be the most important item in hospitals in preparation for a second wave. The most important policy to be implemented at the national level was securing national hospitals designated for the treatment of ID (67.4%). ID experts in South Korea believe that the COVID-19 pandemic may not be easily controlled and that a second nationwide wave is likely to occur in South Korea. Our results indicate that Korean ID specialists believe that a high level of preparation is needed in various aspects, including the procurement of personal protective equipment, to respond efficiently to a second outbreak.